Optimization of silver nanoparticle synthesis by chemical reduction and evaluation of its antimicrobial and toxic activity (2019)
ABSTRACT: Background: Chemical reduction has become an accessible and useful alternative to obtain silver nanoparticles (AgNPs). However, its toxicity capacity depends on multiple variables that generate differences in the ability to inhibit the growth of microorganisms. Thus, optimazing parameters for the synthesis of AgNPs can increase its antimicrobial capacity by improving its physical-chemical properties. Methods: In this study a Face Centered Central Composite Design (FCCCD) was carried out with four parameters: AgNO3 concentration, sodium citrate (TSC) concentration, NaBH4 concentration and the pH of the reaction with the objective of inhibit the growth of microorganisms. The response variables were the average size of AgNPs, the peak with the greatest intensity in the size distribution, the polydispersity of the nanoparticle size and the yield of the process. AgNPs obtained from the optimization were characterized physically and chemically. The antimicrobial activity of optimized AgNPs was evaluated against Staphylococcus aureus, Escherichia coli, Escherichia coli AmpC resistant, and Candida albicans and compared with AgNPs before optimization. In addition, the cytotoxicity of the optimized AgNPs was evaluated by the colorimetric assay MTT (3- (4,5- Dimethylthiazol- 2- yl)- 2, 5 - Diphenyltetrazolium Bromide). Results: It was found that the four factors studied were significant for the response variables, and a significant model (p < 0.05) was obtained for each variable. The optimal conditions were 8 for pH and 0.01 M, 0.0 6M, 0.01 M for the concentration of TSC, AgNO3, and NaBH4, respectively. Optimized AgNPs spherical and hemispherical were obtained, and 67.66% of it had a diameter less than 10.30 nm. A minimum bactericidal concentration (MBC) and minimum fungicidal Concentration (MFC) of optimized AgNPs was found against Staphylococcus aureus, Escherichia coli, Escherichia coli AmpC resistant, and Candida albicans at 19.89, 9.94, 9.94, 2.08 μg/mL, respectively. Furthermore, the lethal concentration 50 (LC50) of optimized AgNPs was found on 19.11 μg/mL and 19.60 μg/mL to Vero and NiH3T3 cells, respectively. Conclusions: It was found that the factors studied were significant for the variable responses and the optimization process used was effective to improve the antimicrobial activity of the AgNPs.